Perioperative Management on Septic Condition et Causa General Peritonitis: Case Report - Handoko, Adelia; Gemawan, Taufiq; Muhammad Rizal Hadi Pratama; Kristianingrum Dian Sofiana; Amien, Muhammad Isryad (Faculty of Medicine, University of Jember, 2023)
Sepsis is a life-threatening systemic pathological condition. Based on WHO, there were 48.9 million cases with 11 million related deaths worldwide in 2017, which is almost 20% of all deaths from disease. Nearly half of all sepsis cases globally occurred in children, with an estimated 20 million cases and 2.9 million deaths. One of the conditions that can cause sepsis is generalized peritonitis. This study is a case report. Primary data was obtained through anamnesis, physical examination, laboratory test and radiology examination. In this case report, a 13-year-old child patient with generalized peritonitis was found due to obstructive ileus causing intestinal perforation, accompanied by sepsis, and underwent laparotomy and colostomy. Appropriate perioperative management is necessary to maintain hemodynamic stability and adequate oxygenation given the presence of sepsis in the patient.